THE EMPLOYEES' PERCEPTIONS OF LEARNING ENGLISH IN A BUSINESS CONTEXT - suningsih, sri; Ciptawaty, Ukhti; Nabila, Nuzul Inas; Wazia, Winia (International Journal of Economics, Business, and Entrepreneurship, 2021)
This study aims to investigate how the English is used in the business workplace. The researcher used a quantitative and descriptive qualitative method. The data used in this study are from open-ended questionnaire to the employees working in economics and business. The results showed that of the 17 worker participants, 11 participants (36.67%) thought that reading was most useful in the workplace, such as analyzing or auditing financial reports, preparing documents and calculating bills, operating software and understanding documents of export and import goods, processing data on a computer, using applications related to data calculation input, studying information about international bank rules, reading journals, opening current and personal savings accounts, reading financial reports, and other activities. Meanwhile, 9 participants (30%) agreed that speaking skills are often used in the workplace. The speaking activity is serving customers from various countries, being interviewed in the recruitment process. Listening skills were obtained by 5 participants (16.67%), which mean that they are rarely applied by the participants. In applying Listening skills, participants use them in understanding conversations. There were 5 participants (16.67%) who chose writing such as answering emails, writing essays, opening checking accounts, and saving savings, making financial reports. The result also reflects the workers’ learning experiences while learning English in the colleges that show several topic discussion they learnt such as Introduction, and general English, the topics about finance/ accounting, financial reports, venture capital, stocks and bonds, which are usually useful in meetings with foreign principals or other employees and the supervisor, writing, reading, discussion, communication, vocabularies, determination of the stock price index, management, recruitment, accounting, financial statement, Learn accounting in English and also conversation is very useful at work, and vocabularies about accounts related to financial statements. In addition, other participants responded that English learnt on campus and applied at work are different. Not all English skills are applied in the respondents' workplace, only reading is used most often. In term of English needs in the workplace, the professionals also need Speaking skills and English terms in the business context.